If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -5) = -11.5 Reorder the terms: 5(-5 + x) = -11.5 (-5 * 5 + x * 5) = -11.5 (-25 + 5x) = -11.5 Solving -25 + 5x = -11.5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 5x = -11.5 + 25 Combine like terms: -25 + 25 = 0 0 + 5x = -11.5 + 25 5x = -11.5 + 25 Combine like terms: -11.5 + 25 = 13.5 5x = 13.5 Divide each side by '5'. x = 2.7 Simplifying x = 2.7
| 3(a+5)=35.1 | | 8.3=3c-1 | | 9e-2=28.6 | | 2p=6.8 | | Y=30x+216 | | (X*X)+15=11 | | 53=6x-1 | | 0=-4+x+0.75x^2 | | X*2+15=11 | | 5m-10-4m-7=0 | | k-8/3=19/3 | | 1600-2Q= | | 3sin(2x+10)=2 | | -2.4+j=-1.8 | | 1700-2Q= | | -10(s+4)=-106 | | Z^4=6z^2+7 | | 5(y+-4)=35 | | 5y+4=35 | | 27=3(2x-3) | | 4-5x+20-6x=68 | | 8x+28=4(x+5) | | -36=8x-11x | | 8(x-10)=-92 | | (x-8)+x+(x+x-8)*0.75=70 | | (x^2+x)-(x+2)=0 | | (1,06²²-1)/(1,06²²,065) | | 7/2x=105 | | 2x+3(4+4)=2x+3(4) | | 422/x=9 | | -10x=10-10 | | Tan-1(8/3)=69.4 |